Nanostructure of the H-terminated p-Si(111)/ionic liquid interface and the effect of added lithium salt. Issue 1 (8th December 2016) - Hoffmann, Viktor; Lahiri, Abhishek; Borisenko, Natalia; Carstens, Timo; Pulletikurthi, Giridhar; Borodin, Andriy; Atkin, Rob; Endres, Frank
Abstract : AFM images of the ionic liquid/H-terminated p-Si(111) interface showing an ordered structure of 3.8 nm in size. Abstract : Ionic liquids are potential electrolytes for safe lithium-ion batteries (LIB). Recent research has probed the use of silicon as an anode material for LIB with various electrolytes. However, the nanostructure of the ionic liquid/Si interface is unknown. The present communication probes the hydrogen terminated p-Si(111) interface using atomic force microscopy (AFM) in 1-ethyl-3-methylimidazolium bis(trifluoromethlysulfonyl)amide ([EMIm]TFSA) and 1-butyl-1-methylpyrrolidinium bis(trifluoromethlysulfonyl)amide ([Py1, 4 ]TFSA). AFM measurements reveal that the imidazolium cation adsorbs at the H-Si(111)/[EMIm]TFSA interface leading to an ordered clustered facet structure of ∼3.8 nm in size. In comparison, the Si(111)/[Py1, 4 ]TFSA interface appeared the same as the native surface in argon. For both pure ILs, repulsive forces were measured as the tip approached the surface. On addition of LiTFSA attractive forces were measured, revealing marked changes in the interfacial structure.